Mucosal immunity to the hookworm Ancylostoma ceylanicum - Alkazmi, Luay Mahmood M. A. (2004)
The host-parasite relationship of the hookworm Ancylostoma ceylanicum was explored in a hamster model system, focusing on intestinal mucosal responses to infection.